2012
DOI: 10.3844/jssp.2012.95.103
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety and Foreign Language Reading Anxiety in a Reading-Proficiency Test

Abstract: Problem statement:The impact of foreign-language anxiety has been researched with respect to the reading domain; however, how it affects reading proficiency in relation to test anxiety in a test situation is yet to be explored. Approach: This study investigated possible relationships between test anxiety, foreign language reading anxiety and English reading proficiency by using scales published in previous studies. A total of 302 EFL college freshmen enrolled in Freshman English were assessed with the Test Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…This finding is in accordance with Liu (2012) who found a negative significant relationship between anxiety and reading among 150 EFL freshmen from a university in central Taiwan. It also goes in line with Tsai & Li (2012) who investigated the relationships between anxiety and English reading proficiency of 302 EFL Taiwanese college freshmen enrolled in Freshman English and found that English reading proficiency was negatively related to foreign language reading. Grammar was also negatively significant related to anxiety (r=-.247), and this finding is in accordance with Nahavandi & Mukundan (2013) who investigated the relationship between language anxiety and the four skills of 548 students (elementary to advanced learners) studying in JahadeDaneshgahi institute of Tabriz, Iran.…”
Section: Resultssupporting
confidence: 76%
“…This finding is in accordance with Liu (2012) who found a negative significant relationship between anxiety and reading among 150 EFL freshmen from a university in central Taiwan. It also goes in line with Tsai & Li (2012) who investigated the relationships between anxiety and English reading proficiency of 302 EFL Taiwanese college freshmen enrolled in Freshman English and found that English reading proficiency was negatively related to foreign language reading. Grammar was also negatively significant related to anxiety (r=-.247), and this finding is in accordance with Nahavandi & Mukundan (2013) who investigated the relationship between language anxiety and the four skills of 548 students (elementary to advanced learners) studying in JahadeDaneshgahi institute of Tabriz, Iran.…”
Section: Resultssupporting
confidence: 76%
“…Namely, TA and FLA are related constructs and they are not independent of each other. Current finding is also consistent with previous research (Covington, 1992(Covington, -1998MacIntyre, Noels, & Clement, 1997;Bailey, Onwuegbuzie & Daley, 2000;Koralp, 2005;Önem, 2010;Tsai & Li, 2012;Tsai, 2013;Salehi & Marefat, 2014). Few previous research contended that test anxiety was not related to language anxiety (MacIntyre & Gardner, 1989;Aida, 1994;Matsuda & Gobel, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In the area of reading and testing, Tsai and Li (2012) examined if there is a relationship between test anxiety, foreign language reading anxiety and English reading proficiency. Three instruments were used for collecting data from 302 Taiwanese college students: Test Anxiety Scale, Foreign Language Reading Anxiety Scale and reading comprehension in a simulated General English Proficiency Test.…”
Section: Introductionmentioning
confidence: 99%